Mathematically and biologically consistent framework for presence-absence pairwise indices – Repository Information - Šizling, A.L.; Keil, P.; Tjørve, E.; Tjørve, K.M.C.; Žárský, J.D.; Storch, D. (Zenodo, 2024)
The upload includes the following components: (i) a table of basic definition of presence-absence indices commonly used in ecology, including equations to convert pairs of mutually i-depenent indices to each other; (ii) 20 theses discussing their mutual relationships and meanings; (iii) a calculator to convert any two informationally independent indices into Jaccard similarity and Simpson beta; and (iv) the data utilized in Šizling et al.'s 202x study. Šizling, A.L., P. Keil, E. Tjørve, K.M.C. Tjørve, J.D. Žárský, and D. Storch,.202X. Mathematically and biologically consistent framework for presence-absence indices of diversity. Content: RI1 Repository Information_v0.1.3 (pdf) TABLE R1: Definitions and Scaling Properties pp. 2- 6 THESES T1-T20: Theses and Evidences pp. 7-14 FIGURE R2: Average Values p. 15 FIGURE R3: Interrelated Assemblages p. 16 FIGURE R4: Multisite Version of Equation 2 p. 17 R5: i-Independence of and s-Dependence on Species Richness p. 18 R6: Data Description p. 19 RI2 Data (txt) 1. Incidence Matrix Cryoconites 2. Incidence Matrix Plants 3. Site Details Cryoconites 4. Site Details Plants 5. Indices Cryoconites 6. Indices Plants RI3 Manual_v0.1.3 (pdf) RI4 Calculator v0.1.3 (pdf) RI5 Code_v0.1.3 (pdf) Special thanks to F. He and W. E. Kunin for their comments on the first versions, Z. Sokolíčková, E. Šizlingová for her help in the field, J. Klimešová and A. Bernard for lessons in Arctic plants, and R.K. Colwell and anonymous reviewers for insightful comments. The project was supported by the Czech Science Foundation (EXPRO 20-29554X and GA ČR 19-21341S). We used the Czech Scientific Infrastructure of the University of South Bohemia, J. Svoboda house on Svalbard – CzechPolar2 LM2015078 supported by MŠMT. PK was funded by the European Union (ERC, BEAST, 101044740). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Research Council Executive Agency. Neither the European Union nor the granting authority ...